Catheter Ablation of Atrial Fibrillation: Three-dimensional Transesophageal Echocardiography Provides an Excellent Overview over the Pulmonary Vein Anatomy Facilitating Radiofrequency and Cryoablation Procedures - Klaus Kettering; Felix Gramley; Stephan von Bardeleben (Cardiology and Angiology: An International Journal, 2017)
Background: Catheter of atrial fibrillation is still challenging because of the high degree of variability of the pulmonary vein anatomy. Therefore, 3D imaging systems are frequently used prior to an ablation procedure. Three-dimensional transesophageal echocardiography provides an excellent overview over the individual left atrial morphology without some of the limitations associated with other imaging techniques. Methods: In 50 patients, three-dimensional transesophageal echocardiography was performed immediately prior to an ablation procedure. The images were available throughout the ablation procedure. In most of the patients with paroxysmal atrial fibrillation, the cryoablation technique was used (Arctic Front Balloon, CryoCath Technologies/Medtronic; group A2). In the other patients, a circumferential pulmonary vein ablation was performed using the CARTO system (Biosense Webster; group A1 (paroxysmal atrial fibrillation), group B (persistent atrial fibrillation)). Results: A three-dimensional transesophageal echocardiography could be performed successfully in all patients and all four pulmonary vein ostia could be evaluated in 84% of patients. The image quality was excellent in the majority of patients and several variations of the pulmonary vein anatomy could be visualized precisely. The findings obtained by three-dimensional transesophageal echocardiography correlated well with the pulmonary vein angiographies performed during the ablation procedures. At 24-month follow-up, 76% of all patients were free from an arrhythmia recurrence (group A1: 81.8%, group A2: 78.9%, group B: 70.0%). There were no major complications. Conclusions: AF ablation procedures can be performed safely and effectively based on prior 3D TEE imaging.